2017
DOI: 10.1093/infdis/jix622
|View full text |Cite
|
Sign up to set email alerts
|

Posttreatment HRP2 Clearance in Patients with Uncomplicated Plasmodium falciparum Malaria

Abstract: Consistent HRP2 clearance dynamics following successful antimalarial treatment imply a common underlying mechanism of biological clearance. Patients who ultimately did not respond to treatment did not exhibit this same pattern of clearance, even in the absence of other indications of inadequate response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 15 publications
4
70
0
Order By: Relevance
“…The bead suspension array described here can successfully be used as for detection and quantification of PfHRP2 and pLDH in whole blood, eluted DBS and plasma or serum samples. The concentration of eluted PfHRP2 from DBS to be equivalent to approximately a 1:20 dilution from whole blood, similarly to previously reported data (40). Differently, for pLDH we found that antigen concentration in eluted DBS corresponds to a 1:60 whole blood dilution, which differs from previously published data showing no differences in antigen recovery between PfHRP2 and pLDH (20).…”
Section: Discussionsupporting
confidence: 90%
“…The bead suspension array described here can successfully be used as for detection and quantification of PfHRP2 and pLDH in whole blood, eluted DBS and plasma or serum samples. The concentration of eluted PfHRP2 from DBS to be equivalent to approximately a 1:20 dilution from whole blood, similarly to previously reported data (40). Differently, for pLDH we found that antigen concentration in eluted DBS corresponds to a 1:60 whole blood dilution, which differs from previously published data showing no differences in antigen recovery between PfHRP2 and pLDH (20).…”
Section: Discussionsupporting
confidence: 90%
“…Because it is a protein completely exogenous to the human body, with no known homology to other human proteins, the unique nature of HRP2 in sequence and structure may lead to delayed clearance from the human host. HRP2 is produced and excreted into the extracellular matrix in large quantities during the ring, trophozoite, and schizont stages (22), which is one of the reasons why it persists in the circulation (23). When HRP2 is used as a diagnostic marker for clinical cases, it may reflect the total parasite load, rather than current peripheral parasite densities.…”
Section: Discussionmentioning
confidence: 99%
“…If there is synchronization of the parasite cycle, then HRP2 levels might reflect the total load of parasites (including those that are sequestered) even better than a direct parasitological measure. This consideration has motivated the use of HRP2 levels as a measure of total parasite biomass (13,14) but is a disadvantage when HRP2 tests are used to estimate the point prevalence of active infections in population surveys, because HRP2 levels can persist for several weeks after parasites have been cleared (23).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst repeated assessments of parasite density shortly after initiation of treatment provide the most conclusive evidence on (changes in) parasite responsiveness (16), alternative metrics are used to compare the early effects of antimalarials. These include the proportion of individuals with residual parasitemia by microscopy (17) or PCR (3,7) or the concentration of the histidine rich protein-2 parasite antigen (18). The current study, examining the kinetics of mRNA transcripts indicative of ring-stage parasitemia following treatment (10,19), explicitly does not aim to present this measure as a proxy for parasite clearance half-lives or direct evidence of reduced susceptibility of parasites to treatment.…”
Section: Discussionmentioning
confidence: 99%